The Poor and Embarrassing Cousin to the Gentrified Quantitative Academics: What Determines the Sample Size in Qualitative Interview-Based Organization Studies? - Kindsiko, Eneli; Poltimäe, Helen (Forum Qualitative Sozialforschung / Forum: Qualitative Social Research, 2019)
It is essential for scholars to reflect on their research practices and critically assess scientific rigor. In the current article, we aim to critically review the state of qualitative research in organization studies by focusing on trends in sample sizes. Organizational scholars presenting qualitative, interview-based manuscripts tend to face the ongoing challenge of how many interviews are enough. The research reported in this article, covering 11 years and investigating 855 interview-based studies, provides empirical evidence that, across the years, the number of interviews seems to be rather high. The total sample included studies with more than 100 interviews (7% of the sample), more than 50 interviews (34%) and studies with more than 30 interviews (62%). Furthermore, when studies start to increase in sample size, they often do so at the expense of homogeneity across respondents. We conclude by giving some possible explanations for why we are facing such a situation today.